Inclusive Capitalism Based on Binary Economics and Positive International Human Rights in the Age of Artificial Intelligence - Chris Fleissner (Washington University Global Studies Law Review, 2018)
The degree to which wage labor will sustain purchasing power over the long term has become a subject of renewed scrutiny in the twenty-first century. Decreasing labor share of compensation for economic growth and the development of disruptive automation technologies approaching human-level intelligence have invited inquiries into the institutions, rules, and norms driving the generation and distribution of earnings from labor and capital, the concentration of wealth, and access to opportunities to participate in the global economy. This Note considers the role of positive human rights in this context through the lens of a paradigm known as inclusive capitalism based on binary economics (ICBE). This Note argues that ICBE's emphasis on eliminating systemic barriers to the individual's right to acquire capital with the earnings of capital contributes critical insights to the modernization of international human rights discourse, particularly with respect to (1) the right to own and acquire private property, (2) the right to participate in economic development, (3) the right to access and engage in productive employment, and (4) the right to pursue independence and self-development. In each of these arenas, private and public stakeholders stand to profit from a revitalized focus on individual ownership of productive capital.
Keywords: Capitalism; Property Rights; Human Rights; International Law; machines; Artificial Intelligence; AI